Optimizing Niosomal Formulations for Enhanced Cellular Applications - Nilufer Cakir; Naile Ozturk; Asli Kara; Ali Zarrabi; Nur Mustafaoglu (Advances in Pharmacological and Pharmaceutical Sciences)
This study delves into the optimization of niosomal production for biological applications, focusing on their emerging role as amphiphilic nanoparticles derived from nonionic surfactants, poised at the forefront of biomedical research. We aimed to formulate and characterize a diverse array of niosomal nanoparticles, with particular emphasis on process-related parameters and physicochemical characteristics. Critical thresholds for size, polydispersity, and zeta potential were established to identify parameters crucial for optimal niosomal formulations through a comprehensive investigation of concentrations, sonication times, ingredient ratios, and surfactant types. Leveraging MODDE software, we generated 10 optimized formulations from preliminary parameter screening. The proposed experimental model design by the software exhibited acceptable similarity to the obtained experimental results (F-score: 0.83). The criteria for selection of the predicted experimental model formed based on targeted physicochemical considerations. To enhance half-life and penetration, especially in higher electrostatic regions like the central nervous system (CNS), we proposed a neutralized surface charge (−10 to 10 mV) while maintaining size within 100–200 nm and polydispersity below 0.5. Extended stability screening revealed periodic and extended Gaussian distributions for size and zeta potential to minimize flocculation and coagulation caused by neutralized surface charge. Notably, the cellular response performance of optimized niosomes was assessed via cellular binding, uptake, and viability in comparison with liposomes. Glioblastoma cell line (U-87) and granulocyte colony-stimulating factor (G-CSF) containing lymphoblastic leukemia cell line (NFS-60) were chosen to represent tumors developed in the CNS region and white blood cells, respectively, enabling a comprehensive comparative analysis with liposomes. The meticulous comparison between niosomes and liposomes revealed comparable cellular viability profiles on both U-87 and NFS-60 cell lines, highlighting their similarities in cellular interactions. Moreover, selected niosomal formulations demonstrated exceptional cellular uptake, either equaling or surpassing observed liposomal uptake. One of the most promising niosomes was selected and optimized to evaluate drug encapsulation performance of niosomes for further drug delivery adaptations by one of the chemotherapy drugs, paclitaxel (PTX). Cytotoxicity study was established with the most efficiently encapsulated niosomal condition with human-derived fibroblasts (HDFs) and U-87 as the representation of healthy and cancerous cell lines. Results demonstrated 1:100 diluted PTX-loaded niosome in the certain concentration demonstrated favorable toxicity in U-87 than original PTX at the same concentration while not disturbing healthy HDFs. These findings underscore the potential of niosomes for reliable drug delivery, challenging the dominance of liposomal vehicles and presenting economically viable nanocarriers with significant implications for advancing biomedical research.